Réponses

Meilleure réponse !
2012-10-26T17:54:42+02:00

On peut scinder la suite en deux suites géométriques de raison 1/4

1/2;1/8;1/32;1/128;/1/512 dont la somme est \frac{\frac{1}{2}.(\frac{1}{4}^{5}-1)}{\frac{1}{4}-1}=\frac{\frac{1}{2}.(\frac{1}{1024}-1)}{\frac{-3}{4}} =-\frac{2}{3}.-\frac{1023}{1024}=\frac{341}{512}

-(1/4+1/16+1/64+1/256) dont la somme est \frac{1}{4}\frac{(\frac{1}{4}^{4}-1)}{-\frac{3}{4}}=\frac{255}{256}au total on a : \frac{341}{512}-\frac{85}{256}=\frac{341}{512}-\frac{170}{512}=\frac{171}{512}